Flame-retardant adhesive for aluminum cellular board and preparation method of flame-retardant adhesive

By using raw materials such as castor oil and polymerized MDI, combined with nano-vapor phase silica and other fillers, a highly crosslinked polyurethane adhesive is formed, which solves the adhesive bonding, flame retardant and safety on aluminum honeycomb boards. The problem of insufficient performance has achieved higher bonding strength, flame retardant performance and environmental protection performance.

CN119432306APending Publication Date: 2025-02-14SHANGHAI JINQIANG ADHESIVE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411872525.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the use of existing adhesives on aluminum honeycomb boards, there are problems of insufficient adhesive performance, flame retardant performance and safety performance.

Method used

Using castor oil and polymerized MDI as the main raw materials, a highly crosslinked polyurethane network structure is formed through cross-linking and copolymerization reaction, and combining nano-vapor phase silica, activated calcium, calcium oxide and heavy calcium carbonate and other components to optimize the adhesive Composition and structure.

Benefits of technology

It significantly improves the adhesive strength, mechanical strength and flame retardant properties, enhances its weather resistance and environmental protection performance, and is suitable for efficient bonding and fire-proof applications of aluminum honeycomb boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of adhesives, in particular to a flame-retardant adhesive for an aluminum cellular board and a preparation method of the flame-retardant adhesive. The flame-retardant adhesive comprises a component A and a component B, wherein the component A comprises castor oil, a thixotropic agent, a chain extender, active calcium, calcium oxide, calcium carbonate, a molecular sieve, a catalyst, a defoaming agent, a solid flame retardant and a liquid flame retardant; and the component B comprises polymerized MDI (Methane Diphenyl Diisocyanate). The flame-retardant adhesive prepared by the invention has moderate viscosity, relatively high peel strength and excellent flame-retardant property, and is particularly suitable for building materials such as aluminum cellular boards and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adhesives, and in particular to a flame retardant adhesive for an aluminum honeycomb panel and a preparation method thereof. Background Art

[0002] Flame retardant adhesive is a special functional adhesive. Its main feature is flame retardant properties. It can prevent the spread of fire to a certain extent and reduce the harm of fire. Flame retardant is the core component of flame retardant adhesive. Commonly used flame retardants include nano alumina, ammonium phosphate, aluminum hydroxide, etc. These flame retardants can improve the flame retardant properties of materials through various ways such as physical and chemical effects, such as forming a dense carbon layer to isolate oxygen, or releasing moisture to reduce temperature, etc.; with the continuous improvement of environmental protection requirements, modern flame retardant adhesives pay more attention to the improvement of environmental protection performance during the research and development process to reduce pollution to the environment and harm to the human body. Flame retardant adhesives are widely used in the bonding of interior decoration materials, such as wall decoration materials, floors, ceilings, aluminum honeycomb panels, etc. The aluminum core layer of the aluminum honeycomb panel is composed of many small hexagonal units, and a honeycomb structure is formed between the small units, which can not only provide high strength and rigidity, but also ensure the lightweight of the material. Therefore, aluminum honeycomb panels are widely used in the construction field. At present, there are relatively few reports on adhesives suitable for aluminum honeycomb panels.

[0003] Patent CN110951438B discloses a flame-retardant solvent-free two-component polyurethane structural adhesive, which consists of component A and component B. Component A includes polyester polyol, chain extender, flame retardant, environmentally friendly catalyst, and reinforcing filler, and component B includes polymerized MDI and flame retardant. The product has fast curing speed, high bonding strength, excellent flame retardant performance, and low toxicity. However, the adhesive compounded with polyester polyol and MDI may exhibit poor weather resistance, such as easy fading and cracking, and has relatively low viscosity, which is not suitable for use in aluminum honeycomb panels.

[0004] Therefore, how to provide a flame retardant adhesive suitable for aluminum honeycomb panels with good bonding performance, flame retardant performance and safety performance is an industry technical problem that urgently needs to be solved. Summary of the invention

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a flame retardant adhesive for aluminum honeycomb panels, including: component A and component B; wherein component A includes: vegetable oil, thixotropic agent, chain extender, filler, molecular sieve, catalyst, defoaming agent, solid flame retardant, liquid flame retardant; component B includes: polymeric MDI.

[0006] As an implementable example, the vegetable oil includes castor oil.

[0007] As an implementable case, the filler includes: active calcium, calcium oxide, and calcium carbonate.

[0008] As an implementable case, the component A includes, by mass, 30-40 parts of castor oil, 0.1-1 parts of thixotropic agent, 0.5-3 parts of chain extender, 5-10 parts of active calcium, 1-5 parts of calcium oxide, 40-60 parts of calcium carbonate, 5-10 parts of molecular sieves, 0.01-0.1 parts of catalyst, 0.01-0.1 parts of defoaming agent, 3-10 parts of solid flame retardant, and 1-2 parts of liquid flame retardant.

[0009] Furthermore, the component A comprises, by weight: 33.4 parts of castor oil, 0.15 parts of thixotropic agent, 0.73 parts of chain extender, 5.08 parts of active calcium, 1.8 parts of calcium oxide, 47.9 parts of calcium carbonate, 5.4 parts of molecular sieves, 0.07 parts of catalyst, 0.07 parts of defoaming agent, 3.63 parts of solid flame retardant, and 1.45 parts of liquid flame retardant.

[0010] As an implementable case, the castor oil includes: one of primary castor oil, secondary castor oil, and tertiary castor oil.

[0011] Furthermore, the castor oil is first-grade castor oil.

[0012] In the prior art, polyurethane adhesives are generally prepared by reacting polyester polyols or polyether polyols with MDI. However, although the polyurethane adhesive materials prepared from polyester polyols or polyether polyols have excellent material strength and adhesion, their hydrolysis resistance is relatively poor, and there is still room for improvement in peel strength. Therefore, the present invention creatively uses castor oil and polymerized MDI as the main raw materials for reaction to prepare polyurethane flame retardant adhesives. This is mainly because the isocyanate groups (-NCO) in the polymerized MDI molecules have high reactivity and can undergo cross-linking copolymerization with the hydroxyl groups (-OH) in castor oil to form a highly cross-linked polyurethane network structure, thereby improving the strength and toughness of the flame retardant adhesive material. In addition, castor oil, especially the carboxylic acid component in primary castor oil, helps to further improve the viscosity and hardness of the polyurethane adhesive, thereby improving the wear resistance and compression resistance of the flame retardant adhesive material. The linolenic acid component in castor oil can increase the thermal decomposition temperature of the polyurethane flame retardant adhesive material and improve its heat resistance stability. Most importantly, polyester polyols, polyether polyols, etc. are non-renewable resources, while castor oil is a natural renewable resource, so the product provided by the present invention has higher environmental protection.

[0013] As an implementable case, the thixotropic agent includes: one or more of organic bentonite, polyvinyl alcohol, and fumed silica.

[0014] Furthermore, the thixotropic agent is fumed silica.

[0015] Furthermore, the thixotropic agent is nano-fumed silica.

[0016] The diameter of the original particles of nano-fumed silica is extremely small, usually only 7-40nm. The tiny particle size makes its surface energy high and highly active, and it is easy to interact with active calcium, calcium carbonate and other components in the flame-retardant adhesive, significantly improving the tensile strength, tear strength and elongation at break of the flame-retardant adhesive. In addition, nano-fumed silica particles can penetrate into the gaps between the polymer chains of the aluminum honeycomb panel substrate and the adhesive layer. The hydroxyl groups on the surface can form a strong adhesive force with the components such as the polyurethane resin polymer chain in the flame-retardant adhesive, improve the interface strength, and then improve the peel strength; when the nano-fumed silica is evenly dispersed in the flame-retardant adhesive system, a large number of particles form hydrogen bonds through the surface silanol groups, forming a silica aggregate network. The aggregate network structure limits the fluidity of the system, thereby increasing the viscosity of the flame-retardant adhesive.

[0017] As an implementable case, the calcium carbonate includes light calcium carbonate and / or heavy calcium carbonate.

[0018] Furthermore, the calcium carbonate is heavy calcium carbonate.

[0019] Furthermore, the mesh size of the heavy calcium carbonate is 500-1000 mesh.

[0020] Furthermore, the mesh size of the heavy calcium carbonate is 800 meshes.

[0021] As an implementable case, the D50 average particle size of the active calcium is 1-5 μm, and the activation degree is less than 20 mL.

[0022] Furthermore, the D50 average particle size of the active calcium is 2.76-3.65 μm, and the activation degree is less than 10 mL; the model is LD-400C, purchased from Lida Superfine Industry (Suzhou) Co., Ltd.

[0023] The test method for activation degree is: first add 90mL of water to the measuring cylinder, then use a pan to measure 5mL of anhydrous ethanol, pour it into the measuring cylinder and shake it evenly to make the anhydrous ethanol and water miscible. Weigh 10g of activated calcium, shake it up and down 30 times, place it on the table and let it stand for 30 minutes, and read the sedimentation sample scale. The smaller the sedimentation value, the better the activation degree.

[0024] There is no particular limitation on the specifications of calcium oxide in the present invention, and any common commercially available product may be used.

[0025] In the present invention, calcium oxide and heavy calcium carbonate are selected for compounding, which can optimize the distribution of solid fillers in the polyurethane flame retardant adhesive, so that the filler particles are more evenly dispersed in the flame retardant adhesive, and the gaps and defects between the particles are reduced, thereby improving the density and viscosity of the adhesive; in addition, the active calcium is subjected to special surface activation treatment and added to the system to synergize with calcium oxide and heavy calcium carbonate, so that the raw materials of each component of the flame retardant adhesive have better compatibility and bonding force, which is beneficial to enhancing the bonding performance of the flame retardant adhesive, so that the adhesion between the flame retardant adhesive and the adherend aluminum honeycomb panel is stronger, thereby improving the overall bonding strength and mechanical strength of the product.

[0026] As an implementable case, the chain extender includes one or more of 1,3-propylene glycol, 1,4-butanediol, propylene glycol, 1,6-hexanediol, trimethylolpropane, diethylene glycol, and triethylene glycol.

[0027] Furthermore, the chain extender is 1,3-propylene glycol.

[0028] In the preparation process of polyurethane flame retardant adhesive, chain extender reacts with polymerized MDI to extend the length of polymer molecular chain and affect the relationship between hard segment and soft segment of polyurethane. Without chain extender, polyurethane molecular chains may be entangled with each other due to the movement of chain segments, which will limit the mobility of molecular chains and increase the viscosity of the whole flame retardant adhesive system. Although the increase in viscosity can improve the adhesion and bonding performance of flame retardant adhesive, the excessive viscosity of the product is not conducive to the construction and coating of flame retardant adhesive on substrates such as aluminum honeycomb panels, and the practicality of flame retardant adhesive is greatly reduced.

[0029] As an implementable case, the molecular sieve includes at least one of a 3A molecular sieve, a 4A molecular sieve, and a 5A molecular sieve.

[0030] Furthermore, the molecular sieve is 4A molecular sieve.

[0031] As a highly active catalyst, the surface sites of 4A molecular sieve can form hydrogen bonds with reactants in the polyurethane reaction system, thereby accelerating the reaction rate. In addition, the polymerization reaction of castor oil and polymerized MDI will produce carbon dioxide gas, and 4A molecular sieve has excellent adsorption properties, which can adsorb and remove low molecular weight substances or impurities such as moisture and carbon dioxide in the polyurethane reaction system; if these impurities exist in the reaction system, they may interfere with the curing reaction of polyurethane, resulting in a decrease in the viscosity and peel strength of the flame retardant adhesive.

[0032] As an implementable example, the catalyst is an organic amine salt complex that does not contain metal components.

[0033] Furthermore, the catalyst is of grade SA102, purchased from Evonik Industries.

[0034] Some catalysts containing metal components have a significant impact on human health and environmental pollution. Therefore, the present invention selects an organic amine salt complex containing no metal components as a catalyst, especially a catalyst with a grade of SA102. As the catalyst of the present invention, the SA102 catalyst can accelerate the reaction of polymerized MDI and castor oil, so that the flame retardant adhesive reaches a cured state faster, not only making the flame retardant adhesive form a stronger cohesive force, but also enhancing the adhesion between the adhesive and the aluminum honeycomb panel to be bonded. Therefore, the polyurethane flame retardant adhesive using the SA102 catalyst has better bonding performance and higher viscosity, and can be more firmly bonded to various materials.

[0035] As an implementable case, the solid flame retardant includes: one of aluminum oxide, aluminum hydroxide, ammonium polyphosphate, magnesium hydroxide, red phosphorus, antimony trioxide, and zinc borate.

[0036] As an implementable case, the mesh size of the solid flame retardant is 800-2000 mesh.

[0037] Furthermore, the solid flame retardant is aluminum hydroxide with a mesh size of 1000 mesh, purchased from Hefei Zhongke Flame Retardant New Materials Co., Ltd.

[0038] As an implementable case, the brands of the liquid flame retardant include: JLS-APP103N; which can be purchased from Hangzhou JLS Flame Retardant Chemical Co., Ltd.

[0039] The finer the aluminum hydroxide particles (the larger the mesh number), the larger the specific surface area and the larger the contact area with the flame retardant adhesive matrix, thereby increasing the interaction force between the matrix and the matrix, hindering the flow of polyurethane molecules, and causing viscosity to increase. Therefore, the mesh number of aluminum hydroxide needs to be limited in the flame retardant adhesive. In the present invention, the mesh number of aluminum hydroxide is limited to 800-2000, which can make the flame retardant adhesive have a moderate viscosity. In addition, the compounding of solid flame retardants and liquid flame retardants can further improve the flame retardant properties and practical properties of the flame retardant adhesive.

[0040] The present invention does not further limit the type of defoaming agent. Any substance that can effectively eliminate bubbles generated during the processing and make the flame retardant adhesive system more uniform can be used. Its brands include but are not limited to: DF-285, DF-214, DF-2416, DF-2655, DF-233, BYK-065, BYK-021, BYK-054, BYK-024, and SX-08.

[0041] As an implementable example, the grades of the polymeric MDI include PM200 and / or PAPI-135C.

[0042] The preparation method of component A comprises: S1. After evenly mixing castor oil, chain extender and liquid flame retardant, add thixotropic agent and stir to disperse evenly; S2. Add calcium oxide, calcium carbonate, active calcium, molecular sieve and solid flame retardant, and disperse them evenly at high speed at 1000-2000rpm. During the stirring process, the temperature of the reaction system will rise to 70-80℃; S3. Add catalyst and defoamer, disperse evenly, cool to below 50℃ and discharge.

[0043] The second aspect of the present invention provides a method for preparing a flame retardant adhesive for an aluminum honeycomb panel, comprising: mixing component A and component B to obtain.

[0044] Furthermore, the mass ratio of component A to component B is 4:1.

[0045] Beneficial Effects (I) The present invention creatively adopts castor oil and polymerized MDI as the main raw materials to react and prepare the polyurethane flame retardant adhesive, rather than the common polyether polyols or polyester polyols on the market as raw materials, which can improve the viscosity and peel strength of the polyurethane flame retardant adhesive and also help improve the environmental performance of the product.

[0046] (ii) The present invention selects nano-fumed silica as a thixotropic agent, which can work together with other solid fillers to improve the viscosity and peel strength of the flame retardant adhesive.

[0047] (III) In the present invention, the active calcium is compounded with calcium oxide and heavy calcium carbonate to make the flame retardant adhesive have higher bonding strength and mechanical strength.

[0048] (IV) The present invention uses a specific molecular sieve in the raw material system. The molecular sieve can adsorb and remove small molecules or impurities such as water and carbon dioxide in the polyurethane reaction system, thereby improving the viscosity and peel strength of the flame retardant adhesive.

[0049] (V) The present invention can further improve the flame retardant properties and adhesion properties of the flame retardant adhesive by compounding solid flame retardants and liquid flame retardants, making the product more suitable for use in building materials such as aluminum honeycomb panels.

[0050] (VI) The flame retardant adhesive provided by the present invention can be used for bonding 0.1mm aluminum plate, aluminum honeycomb, and 0.1mm aluminum plate three-layer sandwich structure, and is particularly suitable for home decoration fields such as indoor ceilings. DETAILED DESCRIPTION

[0051] Example 1 The first aspect of this example provides a flame retardant adhesive for aluminum honeycomb panels, including: component A and component B; wherein component A includes, by mass, 33.4 parts of castor oil, 0.15 parts of thixotropic agent, 0.73 parts of chain extender, 5.08 parts of active calcium, 1.8 parts of calcium oxide, 47.9 parts of calcium carbonate, 5.4 parts of molecular sieves, 0.07 parts of catalyst, 0.07 parts of defoaming agent, 3.63 parts of solid flame retardant, and 1.45 parts of liquid flame retardant; component B is polymerized MDI.

[0052] The castor oil is first-grade castor oil purchased from Adani Group.

[0053] The thixotropic agent is nano-fumed silica, model AEROSIL 200, purchased from Evonik Industries.

[0054] The chain extender is 1,3-propylene glycol.

[0055] The model of the active calcium is LD-400C, which is purchased from Rieter Superfine Industry (Suzhou) Co., Ltd.

[0056] The calcium oxide is a common commercial product.

[0057] The calcium carbonate is 800-mesh heavy calcium carbonate.

[0058] The molecular sieve is a 4A grade molecular sieve, which is a common commercially available product.

[0059] The catalyst is of grade SA102, purchased from Evonik Industries.

[0060] The defoamer is SX-08, purchased from Jiangsu Sixin Technology Application Research Institute Co., Ltd.

[0061] The solid flame retardant is 1000 mesh aluminum hydroxide purchased from Hefei Zhongke Flame Retardant New Material Co., Ltd.

[0062] The brand of the liquid flame retardant is JLS-APP103N, which is purchased from Hangzhou JLS Flame Retardant Chemical Co., Ltd.

[0063] The grade of the polymeric MDI is PM200, which is purchased from Wanhua Chemical.

[0064] The preparation method of component A comprises: S1. After evenly mixing castor oil, chain extender and liquid flame retardant, add thixotropic agent and stir to disperse evenly; S2. Add calcium oxide, calcium carbonate, active calcium, molecular sieve and solid flame retardant, and disperse them evenly at a high speed of 1500 rpm. During the stirring process, the temperature of the reaction system will rise to 70-80°C; S3. Add catalyst and defoamer, disperse evenly, cool to below 50℃ and discharge.

[0065] The second aspect of this example provides a method for preparing a flame retardant adhesive for aluminum honeycomb panels, comprising: mixing component A and component B to obtain.

[0066] The mass ratio of component A to component B is 4:1.

[0067] Comparative Example 1 The specific implementation of this example is the same as that of Example 1, except that the raw materials in component A do not include solid flame retardant and liquid flame retardant.

[0068] Comparative Example 2 The specific implementation of this example is the same as that of Example 1, except that the raw materials in component A do not include a liquid flame retardant.

[0069] Comparative Example 3 The specific implementation of this example is the same as that of Example 1, except that the mass fraction of the solid flame retardant in component A is 2.63 parts, and the mass fraction of the liquid flame retardant is 2.45 parts.

[0070] Comparative Example 4 The specific implementation of this example is the same as that of Example 1, except that the solid flame retardant aluminum hydroxide in component A is of grade H-WF-08, has a mesh size of 3000, and is purchased from Shengda Aluminum Hydroxide Co., Ltd.

[0071] Comparative Example 5 The specific implementation of this example is the same as that of Example 1, except that the raw materials in component A do not include a chain extender.

[0072] Comparative Example 6 The specific implementation of this example is the same as that of Example 1, except that: the weight portion of castor oil in component A is 29.4 parts, and component A also includes 4 parts of polyether polyol.

[0073] The polyether polyol is WANOL C2004, purchased from Wanhua Chemical.

[0074] Comparative Example 7 The specific implementation of this example is the same as that of Example 1, except that the mass fraction of the molecular sieve in component A is 4.3 parts.

[0075] Comparative Example 8 The specific implementation of this example is the same as that of Example 1, except that the catalyst in component A is dibutyltin dilaurate.

[0076] Comparative Example 9 The specific implementation of this example is the same as that of Example 1, except that the raw materials in component A do not include a thixotropic agent.

[0077] Comparative Example 10 The specific implementation of this example is the same as that of Example 1, except that the raw materials in component A do not include calcium oxide.

[0078] Performance Evaluation 1. Flame retardant test: The flame retardant adhesive glue prepared in Example 1 and Comparative Examples 1-10 was injected into a mold, molded for 3 hours at room temperature, and cut into 6 mm thick test strips; the test sample was burned for 10 seconds, and the time when the sample was extinguished after leaving the flame was recorded; the unit of the flame retardant test result was s.

[0079] 2. Viscosity: The test temperature is 25°C; the appropriate viscosity range is 16000-20000 mPa˙s; the unit of viscosity is mPa˙s.

[0080] 3. Roller peel strength: Test according to national standard GB / T 1457-2005, and calculate the average peel strength on the 1st, 3rd and 7th days; the unit of roller peel strength is (N·mm) / mm.

[0081] The test results of the above tests are detailed in Table 1.

[0082] Table 1

[0083] It can be seen from Example 1 and Comparative Examples 1-4 that only by selecting a specific solid flame retardant and a liquid flame retardant to compound can the flame retardant properties of the flame retardant adhesive be improved.

[0084] It can be seen from Example 1 and Comparative Example 5 that a suitable chain extender can make the flame retardant adhesive have a more moderate viscosity, and the product is easier to construct and coat.

[0085] It can be seen from Example 1 and Comparative Example 6 that only by compounding castor oil and polymerized MDI can the peel strength of the product be further improved.

[0086] It can be seen from Example 1 and Comparative Example 7 that a suitable amount of molecular sieve can improve the peel strength of the flame retardant adhesive.

[0087] It can be seen from Example 1 and Comparative Example 8 that a suitable catalyst can improve the peel strength and environmental performance of the flame retardant adhesive.

[0088] It can be seen from Example 1 and Comparative Example 9 that the thixotropic agent can improve the peel strength and viscosity of the flame retardant adhesive.

[0089] It can be seen from Example 1 and Comparative Example 10 that calcium oxide can improve the peel strength of the flame retardant adhesive.

Claims

1. A flame retardant adhesive for aluminum honeycomb panels, characterized in that: The flame retardant adhesive comprises: component A and component B; wherein the component A comprises, by weight, 30-40 parts of castor oil, 0.1-1 parts of thixotropic agent, 0.5-3 parts of chain extender, 5-10 parts of active calcium, 1-5 parts of calcium oxide, 40-60 parts of calcium carbonate, 5-10 parts of molecular sieve, 0.01-0.1 parts of catalyst, 0.01-0.1 parts of defoaming agent, 3-10 parts of solid flame retardant, and 1-2 parts of liquid flame retardant; the component B comprises: polymeric MDI.

2. The flame retardant adhesive for aluminum honeycomb panels according to claim 1, characterized in that: The thixotropic agent includes: one or more of organic bentonite, polyvinyl alcohol, and fumed silica.

3. The flame retardant adhesive for aluminum honeycomb panels according to claim 1, characterized in that: The D50 average particle size of the active calcium is 1-5 μm, and the activation degree is less than 20 mL.

4. The flame retardant adhesive for aluminum honeycomb panels according to claim 1, characterized in that: The chain extender includes one or more of 1,3-propylene glycol, 1,4-butanediol, glycerol, 1,6-hexanediol, trimethylolpropane, diethylene glycol, and triethylene glycol.

5. The flame retardant adhesive for aluminum honeycomb panels according to claim 1, characterized in that: The molecular sieve includes at least one of 3A molecular sieve, 4A molecular sieve and 5A molecular sieve.

6. The flame retardant adhesive for aluminum honeycomb panels according to claim 1, characterized in that: The catalyst is an organic amine salt complex containing no metal components.

7. The flame retardant adhesive for aluminum honeycomb panels according to claim 1, characterized in that: The solid flame retardant comprises: one of aluminum oxide, aluminum hydroxide, ammonium polyphosphate, magnesium hydroxide, red phosphorus, antimony trioxide and zinc borate.

8. The flame retardant adhesive for aluminum honeycomb panels according to any one of claims 1 to 7, characterized in that: The preparation method of component A comprises: S1. After evenly mixing castor oil, chain extender and liquid flame retardant, add thixotropic agent and stir to disperse evenly; S2, add calcium oxide, calcium carbonate, active calcium, molecular sieve and solid flame retardant, and disperse evenly at high speed at 1000-2000rpm; S3. Add catalyst and defoamer, disperse evenly, cool down, and discharge.

9. A method for preparing a flame retardant adhesive for an aluminum honeycomb panel according to any one of claims 1 to 8, characterized in that: Mix component A and component B to obtain.

Citation Information

Patent Citations

  • A flame-retardant solvent-free two-component polyurethane structural adhesive and its preparation method

    CN110951438B